Developing Halal Tourism from Maqasid Sharia Perspective - Ismanto, Kuat; Ghofur, Abdul; Fakir, Fatima Zahra (Hikmatuna : Journal for Integrative Islamic Studies, 2020)
This paper aims to formulate the relationship between the halal tourism concept and maqasid sharia. This library research collected the data from Arabic books, literature, journal articles, websites, etc, then were analyzed with a content analysis strategy. This study revealed that halal tourism is carried out to realize the benefit of religion (hifdz diin) by applying Islamic teachings in tourism activities. Some of the efforts to keep Islamic teachings are providing places of worship, halal food, halal lodging, halal financial services, and others. On the other hand, maqasid sharia can be the basis for developing halal tourism, along with al-Qur'an, al-Hadith, and other relevant bases. Jaser Auda’s concept of Maqasid Sharia stated that the tourism sector is carried out to improve community welfare. At least, maqasid sharia can reinforce seeing halal tourism from Islamic perspective.